2016
DOI: 10.21276/ijmrp.2016.2.6.009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Depression among Type 2 Diabetic Patients in Tabuk City, Saudi Arabia

Abstract: Background: Compared with patients with diabetes alone, patients with depression and diabetes have been shown to have poorer self-management and poor adherence to antidiabetics, lipid-lowering and antihypertensive treatment. Objectives: To investigate the prevalence and determinants of depression in patients with T2DM attending general hospitals, Tabuk, Saudi Arabia. Subjects and Methods: A cross-sectional community based study was conducted in Tabuk city, Saudi Arabia. A representative random sample of diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(43 reference statements)
1
1
0
Order By: Relevance
“…The prevalence of depression estimated in our study conforms with a study conducted in Tabuk city (78%) including 221 patients with type 2 diabetes [ 17 ]. Another study included 450 patients with type 2 diabetes attending primary healthcare centers, and the prevalence of depression was found to be 33.8% using the Depression, Anxiety and Stress Scale-21 (DASS-21) questionnaire [ 9 ].…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of depression estimated in our study conforms with a study conducted in Tabuk city (78%) including 221 patients with type 2 diabetes [ 17 ]. Another study included 450 patients with type 2 diabetes attending primary healthcare centers, and the prevalence of depression was found to be 33.8% using the Depression, Anxiety and Stress Scale-21 (DASS-21) questionnaire [ 9 ].…”
Section: Discussionsupporting
confidence: 87%
“…The variability in the prevalence of the three disorders may be attributed to sociodemographic factors (gender, age, level of education, socioeconomic status, complications, comorbidities, among others) depending on the context of each country. [ 26 ] However, we need more studies focused on the impact of sociodemographic characteristics to confirm this relationship. Some studies showed that female gender constituted a major risk factor for depression, anxiety and stress with a percentage of approximately 50%–60% in comparison with our study, in which we found a greater predominance.…”
Section: Discussionmentioning
confidence: 99%